Semantic Shift in Emoji Usage Among Generation Z in WhatsApp Group Chats - Sylvia Opoku-Fofie; Kaitlyn Naa Ahima Quarcoo (Journal of Applied Linguistics, 2026)
The meanings of emojis have shifted from just conveying emotions to be complex semiotic symbols. In this ethnographic case study, we investigate how Generation Z repurpose the meanings of emojis during their WhatsApp group interactions. This study is guided by Ullman (1957) and Paul’s (trans, 1970) theoretical frameworks on semantic shift. Using a purposive sampling of six WhatsApp groups (information-oriented, academic 1&2, religious, socialization, business-oriented), the results reveal six semantic-shift patterns which include: Transfer of Meaning (36.2%), Broadening (30.6%), Amelioration (17.5%), Pejoration (10.1%), Narrowing (6.0%), and Degeneration (1.1%). The findings reveal Transfer of Meaning as the predominant semantic shift pattern within the WhatsApp interactions of Generation Z. The conclusion drawn is that emoji semantics is context-driven, making one better appreciate the digital language evolution of the Generation Z cohort. Keywords : Emoji; Semantic Shift; Generation Z; WhatsApp; Digital Communication